2011
DOI: 10.1063/1.3607293
|View full text |Cite
|
Sign up to set email alerts
|

Gapless band structure of PbPdO2: A combined first principles calculation and experimental study

Abstract: We present experimental evidence of the gapless band structure of PbPdO2 by combined x-ray photoemission and x-ray absorption spectra complemented with first principles band structure calculations. The electronic structure near the Fermi level of PbPdO2 is mainly composed of O 2p and Pd 4d bands, constructing the conduction path along the Pd-O layer in PbPdO2. Pd deficiency in PbPdO2 causes decreased O 2p-Pd 4d and increased O 2p-Pb 6p hybridizations, thereby inducing a small band gap and hence reducing conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Half-metallic ferromagnets (HMFs) [1], half-metallic fully compensated ferrimagnets (HMFCFs) [5,6], spin gapless semiconductors (SGSs) [7][8][9][10][11][12][13][14][15][16][17][18], and fully compensated ferromagnetic spin gapless semiconductors (FCF-SGSs) [19][20][21] have recently received considerable interest due to their applications in a number of novel spintronic devices. The energy band diagrams for these four kinds of materials are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Half-metallic ferromagnets (HMFs) [1], half-metallic fully compensated ferrimagnets (HMFCFs) [5,6], spin gapless semiconductors (SGSs) [7][8][9][10][11][12][13][14][15][16][17][18], and fully compensated ferromagnetic spin gapless semiconductors (FCF-SGSs) [19][20][21] have recently received considerable interest due to their applications in a number of novel spintronic devices. The energy band diagrams for these four kinds of materials are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al . 9 found that Pd deficiency in PbPdO 2 would cause increased O 2p-Pb 6p and decreased O 2p-Pd 4d hybridizations, which induces a small band gap and hence reducing conductivity. Srivastava et al .…”
Section: Introductionmentioning
confidence: 99%
“…For performing such explorative studies we focus herein on the system Pb/Pd/O/(OH) since the respective binary hydroxides exhibit low solubilities and can be easily dehydrated. Moreover, known PbPdO 2 , containing the lone pair active ion Pb 2+ and the d 8 configured Pd 2+ ion in square‐planar coordination,14 has recently attracted appreciable interest because experimental as well as theoretical evidence of a gapless band structure has been provided 1519. Doping magnetic ions into such a structure, and into lead palladates in general, might open prospects for special magnetic ground states and unusual magnetotransport properties.…”
Section: Introductionmentioning
confidence: 99%